Regulatory compliance of online vendor selling dental whitening products in New Zealand. Issue 2 (15th March 2023) - Oude-Alink, Christina; Hussaini, Haizal Mohd; Seo, Benedict; Firth, Fiona
ABSTRACT: In recent years, numerous over-the-counter (OTC) tooth whitening products have become available online to meet the demand of consumers wanting a convenient way to whiten their smile. This study investigated whether websites selling OTC whitening products containing hydrogen peroxide to New Zealanders are complying with hazardous substance laws set by the New Zealand Environmental Protection Authority (EPA). The search engine 'Google' was used to identify websites selling and shipping OTC whitening products to New Zealand. Data were collected from these websites and analysed. A total of 24 New Zealand based ( n  = 16) and overseas ( n  = 8) websites were included. Of these, 12 (50%) provided an ingredients list, 1 (4%) mentioned all precautionary statements required by the EPA, and 21 (88%) met the EPA restrictions for supply and application of a hazardous substance. 11 (46%) warned of tooth sensitivity as a potential side-effect and 8 (33%) gave a warning for gingival irritation. Fewer than half (42%) recommended consulting a dental professional before using their product. Over-the-counter tooth whitening products being sold online to New Zealanders may be breaching conditions of the EPA and putting New Zealanders at risk. Legislative changes should be considered to ensure that companies' websites are providing correct precautionary statements.